The contingent equilibrium during imbalanced volcano tourism demand through fee estimation: An empirical analysis of tourism in Mount Etna. (15th August 2022) - Platania, Marco; Sharpley, Richard Anthony John; Rizzo, Marcella; Ruggieri, Giovanni
Abstract: Volcanic sites can be considered strategic areas for conservation and protection policies, but such policies may involve considerable costs However, not only are volcanic sites often integral to the tourism industry and, hence, of potential significant benefit to local economies in general; entrance fee income from tourists can also contribute to management and conservation costs in particular. Nevertheless, seasonal variations in tourism demand, resulting in over-and under-tourism situations, may impact on both the level of income generated as well as on the sustainability of sites Therefore, based on a case study of Mt Etna in Italy, this study considers establishing appropriate entry fee levels for volcano areas. First, a logit model is applied to the relevant socio-demographic and site-specific variables. The entrance fees are estimated on visitors' willingness to pay and demand elasticity. Applying contingent valuation method (CVM), two groups of tourists (high and low season visitors) are identified and surveyed, with each group demonstrating different willingness to pay and elasticity levels. Rather than applying a single fee, different entrance fees for the two groups are found to generate a higher level of revenue for the park's economic equilibrium. In addition, the different entrance fees offer the potential to mitigate the peak effects of over-tourism and support demand during under-tourism, with clear sustainability consequences. The results, which confirm four hypotheses set about Mt. Etna, could facilitate decision-makers in determining a feasible balance between management costs, tourism demand characteristics and protection commitments. Highlights: Volcano Parks need public support to cover the high level of cost management. Two different tariffs for different periods of visitors maximise the park income. Higher tariff applied for visitors in high season contain the over-tourism effects. Lower tariff acceptable from visitors in low season increases the revenues. The two tariffs increase the Volcano Park revenue.